2013
DOI: 10.5483/bmbrep.2013.46.7.250
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 enhances the melanogenesis via MITF-GPNMB pathway

Abstract: Endothelin-1 (ET-1) plays an indispensable role in epidermal pigmentation in hyperpigmentary disorders due to a central role in melanogenesis. Nevertheless, precise mechanism involved in ET-1-induced hyperpigmentation is still undefined. Glycoprotein (transmembrane) non-metastatic melanoma protein b (GPNMB) is a key element in melanosome formation. Therefore, we speculated that GPNMB was correlated with ET-1-induced pigmentation. After culturing with ET-1, melanin synthesis was significantly up-regulated, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Glycoprotein (transmembrane) Nmb (GPNMB) is a normal constituent of melanosomes and is required for UVB or endothelin-1 stimulated melanogenesis (13, 14). Our data demonstrate that GPNMB levels are induced in BRAF mutant melanoma cells in response to clinically indicated BRAF and MEK inhibitors; this is in agreement with previous studies that employed experimental MAPK pathway inhibitors (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoprotein (transmembrane) Nmb (GPNMB) is a normal constituent of melanosomes and is required for UVB or endothelin-1 stimulated melanogenesis (13, 14). Our data demonstrate that GPNMB levels are induced in BRAF mutant melanoma cells in response to clinically indicated BRAF and MEK inhibitors; this is in agreement with previous studies that employed experimental MAPK pathway inhibitors (30).…”
Section: Discussionmentioning
confidence: 99%
“…GPNMB is a heavily glycosylated transmembrane protein that localizes to late stage melanosomes, lysosomes and the cell surface. Moreover, GPNMB is required for melanin production in melanocytes (13, 14). In breast cancer, GPNMB promotes breast tumor migration, invasion and metastasis (1517).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GPNMB likely has some relationship with TDP‐43 in ALS patients. GPNMB is known to bind to certain types of proteins (Li et al, ; Shikano et al, ; Zhang et al, ). Previously, we reported that GPNMB has protective effects in theSOD1 (G93A) mouse model of ALS, and in an in vitro model of ALS (Nagahara et al, ; Nagahara et al, ; Tanaka et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelins (EDNs) are secreted mainly from keratinocytes and bind to EDN receptors on melanocytes to regulate melanogenesis . In response to UV, expression of EDNs is highly elevated to enhance the signalling cascades, among which the EDN1–EDN receptor type B (EDNRB) pathway is considered to play significant role in UVB‐induced pigmentation by modulating MITF phosphorylation in normal human melanocytes …”
Section: Neighbouring Cellsmentioning
confidence: 99%
“…36 In response to UV, expression of EDNs is highly elevated to enhance the signalling cascades, among which the EDN1-EDN receptor type B (EDNRB) pathway is considered to play significant role in UVB-induced pigmentation by modulating MITF phosphorylation in normal human melanocytes. 12,37,38 Nitric oxide (NO), a kind of diffusible free radical gas synthesized by the enzyme NO synthase, is considered to be a main intracellular and intercellular messenger molecule in different cells and tissues. 39 The stimulatory melanogenic effect of paracrine factors produced by keratinocytes in response to UV has been reported to be markedly blocked by NO scavengers in normal human melanocyte and keratinocyte cocultures, suggesting an important role of NO in UV-induced melanogenesis.…”
Section: Scf Edn1mentioning
confidence: 99%